Invasion‐induced root–fungal disruptions alter plant water and nitrogen economies. (23rd March 2021) - Bialic‐Murphy, Lalasia; Smith, Nicholas G.; Voothuluru, Priya; McElderry, Robert M.; Roche, Morgan D.; Cassidy, Steven T.; Kivlin, Stephanie N.; Kalisz, Susan
Abstract: Despite widespread evidence that biological invasion influences both the biotic and abiotic soil environments, the extent to which these two pathways underpin the effects of invasion on plant traits and performance remains unknown. Leveraging a long‐term (14‐year) field experiment, we show that an allelochemical‐producing invader affects plants through biotic mechanisms, altering the soil fungal community composition, with no apparent shifts in soil nutrient availability. Changes in belowground fungal communities resulted in high costs of nutrient uptake for native perennials and a shift in plant traits linked to their water and nutrient use efficiencies. Some plants in the invaded community compensate for the disruption of nutritional symbionts and reduced nutrient provisioning by sanctioning more nitrogen to photosynthesis and expending more water, which demonstrates a trade‐off in trait investment. For the first time, we show that the disruption of belowground nutritional symbionts can drive plants towards alternative regions of their trait space in order to maintain water and nutrient economics. Abstract : Invasion‐induced disruptions of belowground nutritional symbionts result in high costs of nutrient uptake for native plants and a shift in plant traits linked to their water and nutrient use efficiencies. Some native plants appear to compensate for the disruption of root–fungal symbionts and reduced nutrient provisioning by sanctioning more nitrogen to photosynthesis and expending more water, which demonstrates a trade‐off in trait investment.